2007
DOI: 10.1007/s10238-007-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined therapy with ritodrine, erythromycin and verapamil on the frequency of micronuclei in peripheral blood lymphocytes of pregnant women

Abstract: The main aim of this study was to investigate the genotoxic effect of combined pharmacotherapy applied in post-operative treatment of cervical cerclage in pregnant women over six days. This study included 19 phenotypically healthy pregnant women in mid-trimester with a diagnosis of cervical insufficiency, mean age 28+/-5.33. The frequency of micronuclei (MN) was estimated in peripheral blood lymphocytes of patients before surgical intervention and after the end of applied pharmacotherapy by application of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The median MNBN level in mothers was 2.36 per 1,000 cells, which was slightly lower than previously reported levels in literature (Grujicic et al 2007; Milošević-Djordjević et al 2003), as expected from our semiautomated system because of the strict scoring criteria applied for automated image analysis (Decordier et al 2011). MN frequencies increased with age and were higher in maternal samples compared with cord blood, in agreement with the literature (Decordier et al 2007; Levario-Carrillo et al 2005; Lope et al 2010; Pedersen et al 2009, 2010; Stankovic et al 2004).…”
Section: Discussionsupporting
confidence: 53%
“…The median MNBN level in mothers was 2.36 per 1,000 cells, which was slightly lower than previously reported levels in literature (Grujicic et al 2007; Milošević-Djordjević et al 2003), as expected from our semiautomated system because of the strict scoring criteria applied for automated image analysis (Decordier et al 2011). MN frequencies increased with age and were higher in maternal samples compared with cord blood, in agreement with the literature (Decordier et al 2007; Levario-Carrillo et al 2005; Lope et al 2010; Pedersen et al 2009, 2010; Stankovic et al 2004).…”
Section: Discussionsupporting
confidence: 53%
“…Thus, our previously published results on the mothers who received partly the same therapy (Grujičić et al 2007), showed the increase of both number of BN cells containing MN and number of MNs in BN cells. The increase was explained by accumulation of DNA damage as a consequence of the applied therapy.…”
Section: Discussionmentioning
confidence: 64%
“…Not very long ago, in the in vivo study of genotoxicity of anesthetic substances and combined therapy in post-surgical treatment of cervical cerclage based on ritodrine hydrochloride, erythromycin and verapamil, we concluded that the combined pharmacotherapy treatment significantly increased the MN frequency in peripheral blood lymphocytes of pregnant women who received therapy during six days (Grujičić et al 2007).…”
Section: Discussionmentioning
confidence: 93%
“…15 Thus, the same authors 20 reported that the investigated betamimetics (ritodrine, fenoterol and hexoprenaline) combined with verapamil and administered to pregnant women during 7 days to 5 months significantly increased the MN frequency in umbilical blood lymphocytes of neonates, regardless of therapeutic does.…”
Section: Discussionmentioning
confidence: 94%
“…[11][12][13][14] Our previous report showed that combined therapy with ritodrine, verapamil and erythromycin in post-operative treatment of cervical cerclage of pregnant women resulted in statistically significant increase of the MN frequency in the peripheral blood lymphocytes. 15 Therefore, it would be of interest to evaluate in vitro separate and combined genotoxic effect of two medicaments that are widely used in gynecological practice. Here, we are presenting our data from the study on genotoxic potential of ritodrine and verapamil, that were tested for their ability to induce MN in cultured human peripheral lymphocytes of healthy donors.…”
Section: Introductionmentioning
confidence: 99%